Theoretical And Methodological Foundations Of The Formation Of The Organizational And Economic Mechanism Of Business Management (Eurasian Journal of History, Geography and Economics, 2022)
Improving the management system of business activity is an important task for every enterprise, regardless of the form of ownership, the result of activity, and the organizational structure. Successfully solving this task allows small enterprises, firstly, to increase the efficiency of the management system, and secondly, to reduce costs and improve the economic performance of production activities.